The immunotype of acute leukaemia in Kelantan as determined by flow cytometry - Dasgupta, Anil; Jackson, Nicholas; Nor, Norazmi Mohd (1999)
The present study reports the total number of acute leukaemias diagnosed in Kelantan over a period of 36 months by morphology, cytochemistry and flow cytometry or immunophenotype using ten monoclonal antibodies (to cell surface CD or HLA-DR antigens) coupled with fluorescein isothiocyanate (FITC)& phycoerythrin(PE).A total of 69 cases gives an annual incidence of 1.4 per 100,000 population. Acute lymphoblastic Leukaemia (ALL) is more in children and acute myeloblastic leukaemia (AML) at all ages, but increases with age.The racial origin is roughly in proportion to the ethnic make up of Kelantan and the ratio between male and female is 1.1:1.In the older age group,the number of cases is higher in female and in contrast,the number of cases in the younger age group is higher in male.Of these cases, about 50% expressed those antigens which are not associated with the main lineage and were diagnosed as biphenotypic which is higher in this study than those reported elsewhere. The expression of CD34 stem cell antigen with or without CD7 or the expression of CD7 with or without CD34 in AML was statistically significant. Whether the coexpression of antigens and an inverse relationship between AML & B-ALL shown in this study affect the prognosis of the disease remains to be ascertained suggesting that it requires further study with future direction as follows the immunophenotype & karyotype or gene rearrangement,in addition to the traditional microscopy for cell morphology and cytochemistry of peripheral & bone marrow cells,the outcome of chemo or bone marrow therapy, and the long term follow up of cases.Our preliminary data on survival rate is difficult to interpret because of short term follow up and small number of cases.